Fabrication and characterization of Self-Supported NiCo-LDH Arrays for High-performance Supercapacitor (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Electrochemical capacitors have emerged as promising complementary energy storage systems to conventional batteries due to their high-power density, rapid charge–discharge capability, and long cycle life. Extensive research has focused on carbon-based electrode materials, which offer high surface area and good electrical conductivity, enabling enhanced charge storage through electric double-layer mechanisms. However, despite these advantages, the widespread replacement of batteries by electrochemical capacitors remains constrained by limitations associated with electrode materials and fabrication methodologies. In particular, complex synthesis routes, material costs, and scalability challenges continue to impede large-scale industrial deployment. Consequently, the development of cost-effective materials and simplified fabrication strategies remains a critical objective in advancing next-generation supercapacitor technologies. In this paper Nickel–cobalt layered double hydroxide (NiCo-LDH) self-supported electrodes were fabricated via a cost-effective electrodeposition route on hydrophilically treated indium tin oxide substrates for high-performance supercapacitor applications. Surface roughening using potassium permanganate treatment enhanced wettability and effective surface area, while subsequent nickel electroplating reduced substrate resistance from 34.4 Ω to 1.8 Ω, significantly improving charge transport. Field-emission scanning electron microscopy revealed a hierarchical nanosheet morphology with pronounced peaks and valleys, providing abundant electroactive sites for Faradaic reactions.Electrochemical performance was evaluated in 2 M KOH using cyclic voltammetry, galvanostatic charge–discharge, and electrochemical impedance spectroscopy. The electrode exhibited well-defined redox peaks within a potential window of 0–0.55 V and delivered a high areal capacitance of 475 mF cm⁻² at 1 mA cm⁻², retaining 275 mF cm⁻² at 30 mA cm⁻² (42% retention). The small semicircle in Nyquist plots indicates low charge-transfer resistance and efficient ion diffusion. Compared with previously reported carbon-based electrodes and conventional NiCo-LDH systems, the present electrode exhibits competitive areal capacitance and improved conductivity through direct current collector integration. The combination of simple fabrication, reduced internal resistance, and stable electrochemical behavior highlights its potential for scalable industrial energy storage applications such as backup power systems and hybrid capacitive devices.